Prosopis Aficana Stem Bark As An Alternative to Antibiotic Feed Additives in Broiler Chicken Diets: Performance and Carcass Characteristics - Alagbe, J.O; Nwosu, G.C; Omokore, E.A (Research Parks Publishing LLC, 2021)
The aim of the present study was to examine Prosopis aficana stem bark (PASB) as an alternative to antibiotic feed additives in broiler chicken diets: performance and carcass and organ weight. A total of two hundred and fifty (250) one-day old broiler chicks of Arbo-acres strain of mixed sex were allotted into five (5) treatments of 5 replicates consisting of 10 birds each in a completely randomized design. Feed and water were given ad libitum and all necessary management practices were strictly observed throughout the experiment which lasted for 56 days. The dietary treatments include a control diet (T1) with no Prosopis aficana stem bark. PASB was included at 200 g, 400g, 600g and 800g in Treatment 2, 3, 4 and 5 respectively. Results obtained were used to evaluate the growth performance (weight gain, feed intake, feed conversion ratio and mortality), carcass and organ weights. Weight gains (WG), average daily feed intake (ADFI) and feed conversion ratio (FCR) were significantly different (P˂0.05) among the treatments. However, increasing the level of Prosopis aficana stem bark from 200g to 800g tended to increase ADWG and ADFI. Highest mortality was recorded in T1 (1.8 %); none was recorded in the other treatments (P ˂ 0.05). Dressing percentage and organ weights were significantly (P ˂ 0.05) influenced by the different inclusions of PASB. No noticeable inflammation was observed in the internal organs (liver, heart, lungs, spleen and gizzard). It was concluded that PASB is rich in phytochemicals and also has significant therapeutic effects in animals and can be safely included in the diets of birds up to 800 g without any negative effect on the general performance of broiler chicks